2017
DOI: 10.1111/poms.12648
|View full text |Cite
|
Sign up to set email alerts
|

On the Same Page? How Asymmetric Buyer–Supplier Relationships Affect Opportunism and Performance

Abstract: Research on buyer–supplier relationships (BSRs) has often focused on only one side of the relationship and, thus, has tended to overlook asymmetries. Yet, a buyer (supplier) may often deal with a bigger supplier (buyer) or one that has higher levels of trust, respect, and reciprocity. Therefore, we examined how two types of asymmetries—size and relational capital—affect perceived opportunism and performance. We used dyadic data from 106 buyers and their matched suppliers gathered from a survey and an archival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(141 citation statements)
references
References 73 publications
(200 reference statements)
8
132
1
Order By: Relevance
“…It is also worth pointing out that the results from this research serve as a unique corollary to the research on power dynamics as extant research has explored different power levels inherent in the relationship (Villena and Craighead ), whereas this study explores the outcomes related to the application of power, in the form of price concessions granted by suppliers. In other words, rather than studying the conditions of power/dependency dynamics, which can lead to different relational outcomes and potential inequity, this manuscript explores the implications for when the buyer wields power and how suppliers respond to the use of such power in different conditions.…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth pointing out that the results from this research serve as a unique corollary to the research on power dynamics as extant research has explored different power levels inherent in the relationship (Villena and Craighead ), whereas this study explores the outcomes related to the application of power, in the form of price concessions granted by suppliers. In other words, rather than studying the conditions of power/dependency dynamics, which can lead to different relational outcomes and potential inequity, this manuscript explores the implications for when the buyer wields power and how suppliers respond to the use of such power in different conditions.…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 99%
“…Additionally, such inequities can create power imbalances, which have been shown to negatively affect the relationship between parties (Nyaga et al. ) and lead to perceived opportunistic behavior (Villena and Craighead ). Expanding on the above, it has also been shown that such dependence can significantly affect the relationship between trust and resource allocation (Pulles et al.…”
Section: Literature Review: Equity Theory and Buyer–supplier Relationmentioning
confidence: 99%
“…For example, in the context of buyer-supplier asymmetries such as size, relational capital, or commitment (cf. Villena & Craighead, 2016), we believe exchange diffusion could alter asymmetry's effects as illustrated in Figure 2 (relative to power). Thus, we make a broad call to examine exchange diffusion in light of various IOR issues.…”
Section: Discussionmentioning
confidence: 88%
“…Likewise, as scholars target multiple respondents (Roh et al., ), they may find there are significant differences in perceptions of the same supply chain phenomenon (cf. the nascent, but growing research on supply chain asymmetries—Villena & Craighead, ). More broadly, we believe that the pursuit of strong theoretical calibration can yield much more theoretical richness than captured in the past and perhaps allow the field to more fully develop our own body of knowledge—wisdom that we can more confidently disseminate to managers.…”
Section: Discussionmentioning
confidence: 99%